Application of Kass' Snake in Medical Images Segmentation - Alwan, F.A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
A   snake   is   an   energy-minimizing   spline   guided   by   externalconstraint forces and influenced by image forces that pull it toward features such as lines and edges. Snakes are active contour models: they lock onto nearby edges, localizing them accurately. Snakes provide a unified account of a number of visual problems, including detection of edges, lines, and motion tracking. We have used snakes successfully for segmentation, in  which  user-imposed  constraint forces guide the snake near features of interest (anatomical structures). Magnetic Resonance Image (MRI) data set and Ultrasound images are used for our experiments. Good results are obtained,  where  Kass' snake could successfully segment the anatomical structures from MRl and ultrasound images.